أحكام العدة في الفقه الإسلامي والتشريع الأسري الجزائري - بـوقـــــــرة أحمــــد حـويــــــشي جعفــــــــر (جامعة المسيلة, 2022)
تعالج هذه المذكرة موضوع العدة ، تحت عنوان أحكام العدة في الفقه الإسلامي والقانون الجزائري ، وفيها تم عرض لما جاءت به الشريعة الإسلامية فيما يتعلق بموضوع العدة ، وتوضيح موقف الأسري قانون الأسرة الجزائري ومناقشته في كل مسألة وبعض الاجتهادات القضائية التي تخدم موضوع المذكرة، كحل أو تفسير لبعض الإشكالات القضائية فيها، وتشمل الدراسة أنواع العدة وجميع أشكالها ثم الآثار المترتبة عن العدة من نفقة ونسب وميراث ، وما يجب على الزوجة أثناء وبعد التفريق بشتى أشكاله . والموضوع مقسم إلى فصلين ؛ وقد خصص القسم الأول إلى ماهية العدة ، وفيه مبحثان الأول مفهوم العدة ومشروعيتها ، والمبحث الثاني نعالج فيه أنواع العدة وانتقالها.أما الفصل الثاني قد خصص إلى آثار العدة وموقف المشرع الجزائري منها وفيه مبحثان الأول الآثار المادية للعدة والثاني الآثار المعنوية للعدة . وفي الأخير جاءت الخاتمة ملخصة لأهم النتائج والتوصيات . الكلمات المفتاحية: - عدة - نفقة - نسب - قانون - فقه Search summary This memorandum deals with the subject of the kit, under the title provisions of the kit in Islamic jurisprudence and Algerian family law, and in it was presented what the Islamic Sharia brought with regard to the subject of the kit, and clarification of the position of the Algerian family law and its discussion in each issue and some judicial jurisprudence that serves the subject of the note, As a solution or explanation for some of the judicial problems in it, the study includes the types and all forms of the waiting period, then the effects of the waiting period such as alimony, lineage and inheritance, and what the wife must do during and after separation in all its forms. The topic is divided into two chapters; The first section was devoted to the nature of the kit, and in it there are two sections, the first is a concept The kit and its legality, and the second section deals with the types of kit and its transmission. The second chapter has been devoted to the effects of the kit and the position of the Algerian legislator regarding it, and in it there are two sections, the first is the material effects of the kit and the second is the moral effects of the kit. In the end, the conclusion came as a summary of the most important results and recommendations. key words :- Several - alimony - lineage - law – jurisprudence
Keywords: - عدة - نفقة - نسب - قانون - فقه